Awareness and prevalence of the symptoms of testosterone deficiency: a cross-sectional survey of community-dwelling men in the UK - Benedict Hayhoe; Austen El-Osta; Aos Alaa; Vivian N Liu; David Roy Huang (BMJ Open)
Objectives Non-specific symptoms of testosterone deficiency (TD) and lack of awareness impact diagnosis and appropriate treatment. This study aimed to characterise the awareness of key symptoms of TD in community-dwelling men and contextualise this against the reported prevalence of these symptoms.Design Cross-sectional survey comprising 54 questions (including assessment of symptoms as per the qADAM questionnaire and where relevant, men’s experiences while on TD treatment). The survey was distributed through online media channels, Prolific and academic networks.Setting Community-dwelling men in the UK.Outcome measures Associations between age, participant demographics and a ‘positive’ qADAM score were assessed using logistic regression. A positive qADAM score was defined as self-rated ‘poor’ or ‘terrible’ libido or erection strength or rating 3 of the other questionnaire domains as ‘poor’ or ‘terrible’.Results Of 973 men, 49% indicated high likelihood of TD using qADAM scores—5% were formally diagnosed. Men over 50 years of age had 1.54–2.0 times higher odds of TD compared with men aged <40 (p<0.05). 31% reported low libido, 27% reported reduced erectile strength and 26% reported over three symptoms associated with TD. Despite this, 55% were unfamiliar with symptoms/signs associated with TD. Only 7% of individuals expressed satisfaction with their access to low testosterone resources in the UK. Key barriers to seeking medical advice or treatment included lack of awareness of symptoms (39%), financial costs (35%) and stigma surrounding hormonal health (29%).Conclusions Almost half of the responders exhibited a burden of TD-associated symptoms, but under 5% had a formal diagnosis. These findings suggest significant gaps between symptom awareness and access to treatment options.